POSITIONING AND REPOSITIONING: PROFESSIONAL IDENTITY DEVELOPMENT DURING A COUNSELLING INTERNSHIP - Dunstan, Lynn (PINS-Psychology in Society, 2026)
This article is a personal reflection on the unfolding of professional identity during a counselling psychology internship. By exploring the personal processes of positioning and repositioning in both theory and praxis, I attempt to demonstrate an essential premise of postmodern thinking: that identity (and in this case, professional identity) is not a linear, sequential process, but a fluid, dynamic and continuing narrative, constructed in a relational context and shaped both by context and contemporary exchanges. I hope that these reflections may provide other intern psychologists with useful insights into, and a clearer understanding of some of the evolutionary processes that appear to be an integral part of the psychology internship experience. My intention in writing this article is not to present a comprehensive description of all my personal and professional experiences during the 18 months I spent as an intern psychologist. Neither have I aspired to analyse the myriad of micro-processes involved in the internship experience, nor to present a complete expose of every aspect of my professional development during that time. Rather, this article represents a personal account of a journey through a counselling psychology internship, along a path which often led me to the edge of my life experience, opened up areas of self long neglected, and exposed personal, but often masked, prejudices and preferences along the way. Although often uncomfortable, the journey was an interesting and eventful one, filled with trials and tribulations, challenges and questions, confusion and insight. Most of all, it was a journey rich in both personal and professional growth.